Problems in the study of political discourse in cognitive linguistics. (Eurasian Journal of Philology Science and Education, 2015)
The article deals with the problem of political discourse in studies of cognitive linguistics. The main task of Political Linguistic Discourse Analysis is to show the complicated relationship between a language, power and society. Study of Political Linguistic helps to hot only understand better world current events but also realize the role of political leaders and their ways in public manipulation. The author marks that political discourse refers to a special type of communication which is characterized by tho high level manipation in conscience peoples. That’s why defining the process of political communication is very important for using language characteristics as way of affect. Therefore the methods of research of political discourse are pointed to find out the contextual links between the politics and language.
Keywords: political discourse; cognitive linguistics; manipulation; social consciousness; political communication; linguistic analysis of political discourse; political language